Stent patency using competing risk model in unresectable pancreatic cancers inserted with biliary self‐expandable metallic stent. Issue 1 (11th June 2012) - Eum, Young Ook; Kim, Yong‐Tae; Lee, Sang Hyub; Park, Sang Wook; Hwang, Jin‐Hyeok; Yoon, Won Jae; Ryu, Ji Kon; Yoon, Yong Bum; Han, Joon Koo; Yoon, Chang Jin; Cho, Jung‐Hwa; Choi, Yunhee
Abstract : Background and aim: Biliary self‐expandable metallic stents (SEMS) play an important role in the quality of life and palliative treatment in unresectable pancreatic cancer patients. We aimed to determine the factors affecting the patency of biliary SEMS and the survival in unresectable pancreatic cancer with obstructive jaundice. Methods: Considering the competing risk and survival, we retrospectively evaluated the patency in 107 unresectable pancreatic cancer patients with obstructive jaundice who were successfully treated with biliary SEMS from January 2000 to April 2010. Results: There were 107 incidents of biliary drainage that were clinically successful and the overall survival period was a median of 133 days. Stent occlusion before death was observed in 36 (33.6%) of 107 patients. Cumulative stent obstruction rates were4.7%, 16.8%, and 24.4% at 1, 3, and 6 months, respectively. Lower cancer stage (<5 month's hazard ratio [HR] = 2.327, >5 month's HR = 0.108) was only associated with the longer patency of the stents in a multivariable analysis using a Fine and Gray model that considered competing risk. In multivariable analysis, lower cancer stage, uncovered stent and normalized serum bilirubin level were associated with a longer survival period (HR = 2.335, 1.906 and 1.795 respectively, P < 0.05). Conclusion: The patency of biliary SEMS in unresectable pancreatic cancers might be affected by the stage. Lower cancer stage and normalized bilirubin are associated with longer survival.